A Tandem Green–Red Heterodimeric Fluorescent Protein with High FRET Efficiency. (15th November 2016) - Wiens, Matthew D.; Shen, Yi; Li, Xi; Salem, M. Alaraby; Smisdom, Nick; Zhang, Wei; Brown, Alex; Campbell, Robert E.
Abstract: The tetrameric red fluorescent protein from Discosoma sp. coral (DsRed) has previously been engineered to produce dimeric and monomeric fluorescent variants with excitation and emission profiles that span the visible spectrum. The brightest of the effectively monomeric DsRed variants is tdTomato—a tandem fusion of a dimeric DsRed variant. Here we describe the engineering of brighter red (RRvT), green (GGvT), and green–red heterodimeric (GRvT) tdTomato variants. GRvT exhibited 99 % intramolecular FRET efficiency, resulting in long Stokes shift red fluorescence. These new variants could prove useful for multicolor live‐cell imaging applications. Abstract : Fluorescent fruit : Three tandem dimer fluorescent proteins, designated "vine Tomatoes", were engineered and photophysically characterized. These proteins can serve as model systems for studying FRET between chromophores with fixed orientations and could prove to be useful for live‐cell fluorescence imaging.